Use of Handheld Raman Spectroscopy for Intraoperative Differentiation of Normal Brain Tissue From Intracranial Neoplasms in Dogs - Doran, Caitlin E.; Frank, Chad B.; McGrath, Stephanie; Packer, Rebecca A. (Frontiers in Veterinary Science, 2022)
The aim of this study was to assess feasibility and accuracy of a hand-held, intraoperative Raman spectroscopy device as a neuronavigation aid to accurately detect neoplastic tissue from adjacent normal grey and white matter. Although Raman spectra are complicated fingerprints of cell signature, the relative shift corresponding to lipid and protein content (2845 cm-1 and 2930 cm-1, respectively) can provide a rapid assessment of whether tissue is normal white or grey matter versus neoplasia for real-time guidance of tumor resection. Thirteen client owned dogs were initially enrolled in the study. Two were excluded from final analysis due to incomplete data acquisition or lack of neoplastic disease. The diagnoses of the remaining 11 dogs included 6 meningiomas, 2 histiocytic sarcomas, and 3 gliomas. Intraoperatively, interrogated tissues included normal grey and/or white matter and tumor. A total of 5 Raman spectra readings were recorded from the interrogated tissues and samples were submitted for confirmation of Raman spectra by histopathology. A resultant total of 24 samples, 13 from neoplastic tissue and 11 from normal grey or white matter, were used to calculate sensitivity and specificity of Raman spectra compared to histopathology. The handheld Raman spectroscopy device had a sensitivity of 85.7% and specificity of 90% with a positive predictive value of 92.3% and negative predictive value of 81.6%. The Raman device was feasible to use intraoperatively with rapid interpretation of spectra. Raman spectroscopy may be useful for intraoperative guidance of tumor resection.